Technological Inefficiency and the Skewness of the Error Component in Stochastic Frontier Analysis - Martin A. Carree (Tinbergen Institute, 2002)
This paper concentrates on negatively skewed one-sided distributions as an explanation ofthe occurence of positive (negative) skewness in the case of stochastic production (cost) frontieranalysis. It takes as example the binomial distribution that can have negative or positive skewand derives the method-of-moments estimators.
Keywords: 330; production frontier; cost frontier; skewness; binomial distribution.; Technische Effizienz; Theorie